Optimization of the Hydrolysis of Safflower Oil for the Production of Linoleic Acid, Used as Flavor Precursor - Marya Aziz; Florence Husson; Selim Kermasha (International Journal of Food Science)
Commercial lipases, from porcine pancreas (PPL), Candida rugosa (CRL), and Thermomyces lanuginosus (Lipozyme TL IM), were investigated in terms of their efficiency for the hydrolysis of safflower oil (SO) for the liberation of free linoleic acid (LA), used as a flavor precursor. Although PPL, under the optimized conditions, showed a high degree of hydrolysis (91.6%), its low tolerance towards higher substrate concentrations could limit its use for SO hydrolysis. In comparison to the other investigated lipases, Lipozyme TL IM required higher amount of enzyme and an additional 3 h of reaction time to achieve its maximum degree of SO hydrolysis (90.2%). On the basis of the experimental findings, CRL was selected as the most appropriate biocatalyst, with 84.1% degree of hydrolysis. The chromatographic analyses showed that the CRL-hydrolyzed SO is composed mainly of free LA.